2022
DOI: 10.1111/josi.12532
|View full text |Cite
|
Sign up to set email alerts
|

Caste and COVID‐19: Psychosocial disparities amongst rural Indian women during the coronavirus pandemic

Abstract: The COVID-19 pandemic has exacerbated preexisting mental health disparities. In India, marginalization based on caste membership, gender, and rural residence are critical determinants of inequity across the lifespan. Guided by the theoretical frameworks of minority stress and intersectionality, this study examined caste-based disparities in fear of coronavirus (FOC), mental health symptoms, and perceived loneliness amongst rural women in north India during the COVID-19 pandemic. Participants (N = 316) complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 117 publications
(153 reference statements)
0
5
0
Order By: Relevance
“…For example, semistructured interviews with 35 women who were pregnant and/or gave birth during the global pandemic allowed mothers to explain how this unprecedented health crisis impacted their stress, isolation, social support, and coping (Williams et al, 2023). Examinations of class-based differences in women's experiences can be seen in Jiwani et al (2023) study with more than 300 women in India. Through the use of highly structured interviews, this study affords insight into how women of different castes experienced fear, loneliness, depression, anxiety, and stress during the COVID-19 global pandemic.…”
Section: Using Science To Understand How Women's Health and Safety Wa...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, semistructured interviews with 35 women who were pregnant and/or gave birth during the global pandemic allowed mothers to explain how this unprecedented health crisis impacted their stress, isolation, social support, and coping (Williams et al, 2023). Examinations of class-based differences in women's experiences can be seen in Jiwani et al (2023) study with more than 300 women in India. Through the use of highly structured interviews, this study affords insight into how women of different castes experienced fear, loneliness, depression, anxiety, and stress during the COVID-19 global pandemic.…”
Section: Using Science To Understand How Women's Health and Safety Wa...mentioning
confidence: 99%
“…Examinations of class‐based differences in women's experiences can be seen in Jiwani et al. (2023) study with more than 300 women in India. Through the use of highly structured interviews, this study affords insight into how women of different castes experienced fear, loneliness, depression, anxiety, and stress during the COVID‐19 global pandemic.…”
Section: Using Science To Understand How Women's Health and Safety Wa...mentioning
confidence: 99%
See 1 more Smart Citation
“…The size of the beta for this group was larger than the overall sample, indicating that participation in the intervention may have been more beneficial for mothers who identify as low caste. This is significant given that relative to high-caste individuals, low-caste individuals in India face significantly worse outcomes across a range of socioeconomic and health indicators (Bhagavatheeswaran et al, 2016; Chauhan, 2008; Dalal & Lindqvist, 2012; Jiwani et al, 2022; Khubchandani et al, 2018; Thomas et al, 2013). Thus, identifying interventions that can specifically support low-caste families to help infants and toddlers reach their full potential is especially important.…”
Section: Discussionmentioning
confidence: 99%
“…Caste membership has been found to be another critical determinant of wellbeing across the lifespan in India (Human Rights Watch, 2001). Research has consistently demonstrated that relative to high-caste individuals, low-caste individuals experience worse health and social outcomes, including a lower life expectancy (Thomas et al, 2013), worse educational outcomes (Chauhan, 2008), greater perceived discrimination (Bhagavatheeswaran et al, 2016; Khubchandani et al, 2018), worse mental health, and higher exposure to violence (Jiwani et al, 2022b) amongst other disparities. As such, it may be important to include such factors as potential covariates when examining the efficacy of any intervention in the Indian context.…”
Section: Literature Reviewmentioning
confidence: 99%